Gender roles of Filipino men and women - Padilla, Lara Anne Marie D. (1999)
A study on the gender roles of Filipino husbands and wives was investigated from 15 couples equally coming from an urban area, represented by the Barangay 83, Paraiso, San Jose, Tacloban City and a rural barangay, represented by Barangay Maliwaliw, Dagami, Leyte, to a total of 30 couples in all. The researcher conducted an interview to the areas of study, disguisingly asking the sources of the family's income in their places. The thirty couples were asked on who works to earn a living for the family, and who performs the household chores for the family. The researcher aims to find out whether there is a significant difference between the gender roles performed by the husbands and wives. Testing the hypothesis through the Chi-square method, the researcher has found out that, there is no significant difference between the gender roles being performed by the Filipino men and women, both in an urban and rural barangay.